Phenytoin toxicity manifesting as acute psychosis: An uncommon side effect of a common drug - Agrawal, Mohit; Borkar, Sachin; Kale, Shashank (Asian Journal of Neurosurgery, 2019)
Antiepileptic drug-induced psychotic disorder represents an iatrogenic, adverse drug reaction. Phenytoin has rarely been shown to be a causative agent of acute psychosis in patients. We present such a rare case of short term use of phenytoin causing toxicity manifesting as acute psychosis and complete recovery following phenytoin withdrawal.
Keywords: Acute psychosis; phenytoin toxicity; rare side effect